Fresh Properties of Self-Compacted Engineering Cementitious Composites - Amouri, Mohammed Shaker; Fawzi, Nada Mahdi (Engineering, Technology & Applied Science Research, 2025)
Self-Compacting Engineered Cementitious Composites (SC-ECC) integrate the workability and flowability of Self-Compacting Concrete (SCC) with the exquisite ductility of Engineered Cementitious Composites (ECCs). This study investigates the optimization of the clean and hardened properties of SC-ECC by studying the results of PVA fibers, superplasticizer dosage, and fly ash-to-cement ratios. 18 trial mixes were produced and evaluated based on the recommendations of EFNARC (2005). The slump flow ranged from 240 mm to 280 mm, meeting self-compacting requirements, as the compressive strength at 7 days varied between 39 MPa and 59 MPa. The findings underscore the role of these variables in enhancing the overall performance of SC-ECC, making it suitable for modern construction.